ANALYSIS OF SOIL FERTILIZING CAPABILITIES, GROWTH AND ENZYME PRODUCTON STATISTICS FOR SYMBIOTIC NITROGEN FIXING BACTERIA VITSS5 SCREENED FROM PALAR REGION, VELLORE - SAI SHIVA SHANKAR V; SUNEETHA V (International Journal of Pharma and Bio Sciences, 2013)
In this study, the nitrogen fixing bacteria VIT SS 1-6 were screened from the root nodules of Groundnut (Family: Fabaceae, Species: Arachis hypogaea) collected from Vellore district were examined for their plant growth promoting properties. Of the six isolates obtained, five were fast growing and one was slow growing. The slow growing species VIT SS5 was further examined for its nitrogen fixing, potassium and phosphorus solubilising capabilities to identify its level of efficiency over the traditionally used N-nitrogen P-phosphorus K-potassium fertilizer. This particular strain was chosen because it was identified in most of the isolates. Tentative identification was done using biochemical tests and microscopic examination. The screened organism was tested for its enzyme production, utilization of carbohydrate sources, salt, pH and temperature tolerance and statistical analysis was performed. Further studies on preparation of liquid fertiliser will be done.